Implementation of Hygiene and Sanitation Practices in the Hotel Kitchen: A Case Study at Shante Hotel Xitou Taiwan - Suhardin, Stefanus; Trianingrum, Ni Nyoman Nidya; Arini, Ni Nyoman (LPPM Universitas Dhyana Pura, 2026)
This study examines the implementation of hygiene and sanitation practices in the kitchen of Shante Hotel Xitou Taiwan, a three-star hotel located in Nantou County. The background of this research is the rapid growth of tourism in Taiwan, with 4,197,240 foreign visitors recorded in the first half of 2025, which has significantly increased the operational intensity of hotel kitchens, demanding stricter adherence to hygiene and sanitation standards. This research employs a descriptive qualitative method using direct observation with checklist instruments, in-depth interviews with the Head Chef and Senior Cook, and documentation. The findings reveal that personal hygiene implementation remains inconsistent, with staff often failing to wear complete uniforms, hairnets, and food-grade gloves. Food hygiene shows multiple non-compliances including the absence of FIFO application, unlabeled food stocks, cross-contamination risks from shared washing sinks, and improper storage of raw eggs outside the chiller. Workplace sanitation also requires improvement, as evidenced by grease-coated exhaust fans, uncovered waste bins, and damaged kitchen floors. Corrective efforts by management include monthly mandatory staff training, implementation of daily cleaning checklists, facility upgrades such as color-coded cutting boards, segregated wash sinks, and dedicated handwashing stations, as well as periodic external audits. The study concludes that while basic hygiene practices are partially observed, systematic inconsistencies persist and must be addressed through stronger supervisory mechanisms, facility investment, and a culture of food safety compliance.